Physiological and Pathological Aspects of Postpartum Uterine Ulceration in a Domestic Cat - Ahmad Syarifuddin Syarif (Journal of Applied Veterinary Science And Technology, 2026)
Background: Uterine disorders in feline medicine are rarely reported but may result in severe clinical consequences if diagnosis is delayed. Uterine ulceration is an uncommon pathological condition characterized by focal damage to the endometrium that can extend into deeper uterine layers, often associated with inflammation and hemorrhage. Because clinical signs such as lethargy, anorexia, and abnormal vaginal discharge are frequently nonspecific, diagnosis is often delayed. Purpose: This case report describes the clinical presentation, diagnostic findings, and therapeutic management of uterine ulceration in a cat, with emphasis on uterine hemorrhage as an important diagnostic indicator. Case(s): Female cat was presented with a history of hyporexia, lethargy, and intermittent hemorrhagic vaginal discharge. Physical examination revealed pale mucous membranes, mild dehydration, and abdominal pain upon palpation. Hematological analysis showed mild anemia and leukocytosis, indicating ongoing blood loss and systemic inflammation. Ultrasonographic examination identified irregular thickening of the uterine wall and echogenic intraluminal material, findings consistent with uterine hemorrhage. Based on these findings, uterine ulceration was considered the primary diagnosis. Case Management: Patient was stabilized using intravenous fluid therapy along with antibiotics, analgesics, and anti-inflammatory drugs. Due to persistent uterine bleeding, ovariohysterectomy was performed as definitive treatment, and the diagnosis was confirmed through gross and histopathological evaluation. Conclusion: Uterine ulceration with hemorrhage is a rare but important condition in cats. Early recognition and appropriate management can result in favorable outcomes.